THE FA'IL PRINCIPLE IN THE MORALS AND ETHICS OF A MUSLIM - Annisa Eka Putri Aulia; Chairun Nisa; Rofiqo Hasanah Saragih (Yayasan Haiah Nusratul Islam, Indonesia, 2025)
This study aims to examine the relationship between fa'il rules in Arabic grammar and the formation of the morals of a Muslim. So far, learning Arabic rules tends to be technical-linguistic, without linking grammatical structures to the value of character education and Islamic spirituality. In fact, the fa'il element as the actor in a verbal sentence reflects the concept of personal responsibility for an action, as emphasized in Islamic teachings, especially in QS. Az-Zalzalah verses 7-8. This research applies a descriptive qualitative approach through a literature study of classical nahwu books, Qur'anic verses, hadith, and contemporary Islamic education literature. The results show that understanding the fa'il rule not only improves the ability of language structure, but also fosters ethical awareness in students regarding every action has a perpetrator who will be held accountable. The integration between linguistic understanding and value education produces an Arabic learning model that is not only oriented to grammatical aspects, but also supports character building. In the context of Islamic education, the teacher acts as a value facilitator by linking the fa'il element in the sentence with individual responsibility in real life. Therefore, the structure of Arabic, especially the fa'il element, can be a strategic instrument in moral education. This finding shows the importance of an integrative approach in learning Arabic in order to form moral people who are not only good at language, but also aware of their spiritual and social responsibilities as fa'il al-hayah (actors in life).